Selected Performance for Cyprus Choreography Showcase Festival - Korae, Eva (My University, 2026)
LOITERING a performance by Arianna Marcoulides in collaboration with Eleana Alexandrou, Eva Korae and Panos Bartzis. LOITERING means to stand or wait somewhere without an obvious purpose. We are waiting for something to happen. We are waiting for something to change. All we do is walk in anticipation. The earth is about to explode. If we die tomorrow, we die. Someone please save us. This is a piece about waiting. This is a piece about acting. This is a piece about time. This is a piece about the world. This is a piece about the state we are in today. This is a piece about us. What are you going to do about it? Team: Conceived and choreographed by Arianna Marcoulides Performers: Eleana Alexandrou, Arianna Marcoulides Stage Design and making*: Eva Korae Sound Design: Panos Bartzis Light Design: Evripides Dikaios Poster Graphics: Nektaria Constantinou Produced by bytheway productions
Keywords: Arts and entertainment